Analisis Kalimat Interogatif dalam Talkshow Mata Najwa - Bella Rezkita Shelanda; S, Ermawati (UIR PRESS, 2021)
This research is motivated by the existence of interrogative sentences in the Mata Najwa Talkshow which are influencing the listeners. The problems studied in this research are (1) What is the form of interrogative sentences asking for confession in the Mata Najwa Talkshow? (2) How is the form of an interrogative sentence that asks for an answer about one element of the sentence formed with the help of a question word in the Mata Najwa Talkshow? (3) What is the form of an interrogative sentence that asks for an answer in the form of a 'reason' in the Mata Najwa Talkshow? (4) What is the form of an interrogative sentence that asks for an answer in the form of an opinion in the Mata Najwa Talkshow? (5) What is the correct form of interrogative sentences in the Mata Najwa Talkshow?. The purpose of this study is to describe, analyze, interpret, and conclude the form of interrogative sentences that ask for confessions, ask for answers from question word elements, ask for reasons, ask for opinions and present them in the Mata Najwa Talkshow. The theory used to analyze the research problem is the theory proposed by Chaer (2009), Ramlan (2005), and other supporting theories. The approach in this research is a qualitative approach using content analysis method. The type of research conducted includes satisfaction research. Based on the analysis carried out, found 40 data regarding the form of interrogative sentences that ask for confession of 6 data, ask for answers from question word elements with 24 data, ask for reasons for 2 data, and ask for opinions on 8 data. No correct interrogative sentence found. The results and conclusions of this study are (1) interrogative sentences that ask for recognition found in the Mata Najwa Talkshow include interrogative sentences that ask for answers in the form of